The Effect of Environmental Concerns and Government Policies on The Intention to Buy Electric Car - Alfy Sukma; Arif Imam Suroso; Irman Hermadi (School of Business, IPB University (SB-IPB), 2023)
The electric car market in Indonesia is still relatively weak, even though electric cars have a positive impact on the environment. The Indonesian government supports the growth and development of electric vehicles by issuing several policies to attract people's purchasing intentions in Indonesia. This study analyzes environmental concern and government policy that influence the purchase intention of electric car in Indonesia through extended theory of planned behavior concept and understands the characteristics of respondents and formulates managerial implications to increase the purchase intention of electric cars in Indonesia. The analysis in this study uses Partial Least Square Structural Equation Modeling (PLS-SEM) with 100 respondents. The results obtained in terms of public perception of people's purchase intention to support the sale of electric cars, where the variables of attitude, behavior control, environmental concern, and government policies have a good perception of the intention to buy electric cars, and neutral perception for the subjective norm variable. Environmental concern and government policies have a positive and significant effect on the intention to buy an electric car. Increase environmental awareness, control behavior, attitudes, subjective norms, and government policies as the main strategy in increasing the intention to buy electric cars Keywords: environmental concern, government policy, theory of planned behavior, purchased intention, electric car